Organic chemistry - Harold Hart (Houghton Mifflin, 2007)
Designed specifically for the one-semester short course in organic chemistry, this market leader appeals to a range of non-chemistry science majors through its emphasis on practical, real-life applications of chemistry, coverage of basic concepts, and engaging visual style. In contrast to competitors who offer mainly streamlined versions of full-year texts, this text has always been aimed at the short course and its writing style, approach, and selection of topics best suit the needs of this market. The Twelfth Edition further develops the strengths of the previous editions through an updated, dynamic art program--online, on CD, and in the text--new content to keep students current with developments in the organic chemistry field, and a revised lab manual